The responses of cancer cells to PLK1 inhibitors reveal a novel protective role for p53 in maintaining centrosome separation. - Smith,L; Farzan,R; Ali,S; Buluwela,L; Saurin,A; Meek,DW (Scientific Reports, 2017)
Polo-like kinase-1 (PLK1) plays a major role in driving mitotic events, including centrosome disjunction and separation, and is frequently over-expressed in human cancers. PLK1 inhibition is a promising therapeutic strategy and works by arresting cells in mitosis due to monopolar spindles. The p53 tumour suppressor protein is a short-lived transcription factor that can inhibit the growth, or stimulate the death, of developing cancer cells. Curiously, although p53 normally acts in an anti-cancer capacity, it can offer significant protection against inhibitors of PLK1, but the events underpinning this effect are not known. Here, we show that functional p53 reduces the sensitivity to PLK1 inhibitors by permitting centrosome separation to occur, allowing cells to traverse mitosis and re-enter cycle with a normal complement of 2N chromosomes. Protection entails the activation of p53 through the DNA damage-response enzymes, ATM and ATR, and requires the phosphorylation of p53 at the key regulatory site, Ser15. These data highlight a previously unrecognised link between p53, PLK1 and centrosome separation that has therapeutic implications for the use of PLK1 inhibitors in the clinic.